Education on Tree Planting and Its Benefits for the Environmental Ecosystem at Madrasah Ibtidaiyah Siondop Julu - Siregar, Nurul Husna; Gaja, Rahmadani; Salsabilah, Novi; Lumbantobing, Riza Agita (Faculty of Mathematics and Natural Sciences, University of Jember, 2026)
This community service program was conducted as an effort to promote environmental awareness from an early age through tree-planting activities in the school environment. Tree planting not only contributes to environmental sustainability but also serves as an effective learning medium for fostering environmentally responsible attitudes among elementary school students. Therefore, educational activities that actively engage students are essential for developing positive habits and environmental stewardship from an early age. Based on this background, the program aims to enhance the knowledge and skills of sixth-grade students at a Madrasah Ibtidaiyah regarding environmental conservation through tree-planting activities. The implementation method included educational sessions on the ecological importance of trees, the benefits of school greening programs, and proper tree-planting techniques. Following the theoretical session, students engaged in hands-on tree-planting activities in designated areas of the school under the guidance of the program team. The results indicated an improvement in students' understanding of environmental conservation and the benefits of trees for both human life and ecosystems. The students were able to demonstrate basic tree-planting skills correctly and showed increased concern for environmental preservation. Their enthusiasm throughout the activities suggests that practice-based learning is an effective approach for environmental education at the elementary school level. This program is expected to serve as an initial step toward fostering sustainable environmental awareness and positive environmental behaviors among students, both within the school setting and in the broader community.